IMPROVING STUDENTS’ ABILITY IN WRITING RECOUNT TEXT USING GUIDED WH-QUESTIONS - Pratiwi, Wenny; Regina, Regina; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to improve students’ ability in writing recount text using guided wh-questions to class VIII C students of SMP Negeri 6 Teluk Keramat in Academic Year 2018/2019. This research was conducted based on the problems found in the classroom. First, students had difficulty in writing recount text because they did not know about the generic structures. Second, students also had difficulties in using simple past tense. The research was conduted using Classroom Action Research in three cycles. The subject of this research was 26 students in class VIII C. The researcher used observational checklists, field notes, and scoring rubric as tools to collect the data. The result showed that the use of guided wh-questions can generate the students’ ideas and develop the ideas in writing. Guided wh-questions was improved students’ achievement in writing recount text concerning the generic structure, language features, and writing mechanics. Keyword: Improve, Writing Recount Text, Guided WH-Questions.